Prinsip Enam Benar dalam Pemberian Obat Pasien di Ruang Rawat Inap RSUD Kabupaten Jember - Utama, Bagus Pria; Purwandari, Retno; Kurniawan, Dicky Endrian (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Applying the principle of six correct administration of drugs by nurses is one of the preventiveimplementations of patient safety. It can guarantee the safety of treatment for patients, reduce medicationerrors, and avoid giving the wrong medication to patients in the hospital. This study aimed to explore theprinciple of six correct drug administration implementation by nurses in the hospital. A descriptive methodapproach was used. This study was conducted in two general hospitals in Jember and followed by 75 inpatientward nurses through the total sampling technique. The results of this study showed that the modus value ofthe implementation of the six-correct principles is 125, the data position is in the middle position of thedispersion, which means the implementation of the principle of six correct by nurse approaching themaximum value. The data also showed that the nurses still did not entirely implement the principle of sixcorrect in drug administration. Nurse managers can enhance the implementation of the principle of six bynurses through supervision activities. In addition, it is necessary to have an evaluation conducted by thehospital patient safety commission on the implementation of the principle of six correct drug administrationsby inpatient ward nurses